Answer:
Question one solution: (-5,4)
Question two solution: (3,1)
Explanation:
Remark
Both of these work better with substitution. When a y (or x) in two equations sits by itself on one side of the equation, substitution is the method of choice.
These two questions are a perfect example of when you can use substitution. You have "y"s sitting on one side of the equation alone and without coefficients.
y = -2x - 6
y = -2x - 6
y = x + 9
The "y"s must be equal when you are finished so they can be equated.
x + 9 = - 2x - 6 Add 2x to both sides
x + 2x + 9 = -2x + 2x -6 Combine like terms
3x + 9 = - 6 Subtract 9 from both sides
3x + 9 - 9 = - 6 - 9 Combine
3x = - 15 Divide by 3
3x/3 = - 15/3 Do the division
x = - 5
============================
Now solve for y
y = x + 9
y = -5 + 9
y = 4
y = - x + 4
y = - x + 4
y = 5x - 14
Equate the y's
5x- 14 = -x + 4 Add x to both sides
5x + x - 14 = -x + x + 4 Combine
6x - 14= 4 Add 14 to both sides
6x - 14 + 14 = 4 + 14 Combine
6x = 18 Divide by 6
6x/6 = 18/6 Do the division
x = 3
============================
Solve for y
y = -x + 4
y = -3 + 4
y = 1